Mechanism of Protein Kinase B Activation by Cyclic AMP-Dependent Protein Kinase - Filippa, Nathalie (American Society for Microbiology, 1999)
Activation of protein kinase B (PKB) by growth factors and hormones has been demonstrated to proceed via phosphatidylinositol 3-kinase (PI3-kinase). In this report, we show that PKB can also be activated by PKA (cyclic AMP [cAMP]-dependent protein kinase) through a PI3-kinase-independent pathway. Although this activation required phosphorylation of PKB, PKB is not likely to be a physiological substrate of PKA since a mutation in the sole PKA consensus phosphorylation site of PKB did not abolish PKA-induced activation of PKB. In addition, mechanistically, this activation was different from that of growth factors since it did not require phosphorylation of the S473 residue, which is essential for full PKB activation induced by insulin. These data were supported by the fact that mutation of residue S473 of PKB to alanine did not prevent it from being activated by forskolin. Moreover, phosphopeptide maps of overexpressed PKB from COS cells showed differences between insulin- and forskolin-stimulated cells that pointed to distinct activation mechanisms of PKB depending on whether insulin or cAMP was used. We looked at events downstream of PKB and found that PKA activation of PKB led to the phosphorylation and inhibition of glycogen synthase kinase-3 (GSK-3) activity, a known in vivo substrate of PKB. Overexpression of a dominant negative PKB led to the loss of inhibition of GSK-3 in both insulin- and forskolin-treated cells, demonstrating that PKB was responsible for this inhibition in both cases. Finally, we show by confocal microscopy that forskolin, similar to insulin, was able to induce translocation of PKB to the plasma membrane. This process was inhibited by high concentrations of wortmannin (300 nM), suggesting that forskolin-induced PKB movement may require phospholipids, which are probably not generated by class I or class III PI3-kinase. However, high concentrations of wortmannin did not abolish PKB activation, which demonstrates that translocation per se is not important for PKA-induced PKB activation.